Highly efficient and stable Si photocathode with hierarchical MoS2/Ni3S2 catalyst for solar hydrogen production in alkaline media. (May 2020) - Fan, Ronglei; Zhou, Ju; Xun, Wei; Cheng, Shaobo; Vanka, Srinivas; Cai, Tianyi; Ju, Sheng; Mi, Zetian; Shen, Mingrong
Abstract: Designing highly efficient and stable Si photocathodes for solar hydrogen production in alkaline electrolytes is especially challenging due to the sluggish surface kinetics for hydrogen evolution reaction (HER) and unsuccessful contact between the catalyst and Si substrate. Herein, a facile electrodeposition process is reported to integrate the hierarchical MoS2 /Ni3 S2 structure as a catalyst layer onto the surface of Ni protected Si photocathode. Rough surface morphology and obvious electronic interactions between Ni3 S2 and MoS2 were observed experimentally, while the theoretical calculation illustrated that the atomic mixed MoS2 /Ni3 S2 interfaces enhance the hydrogen-adsorption of MoS2 and hydroxide adsorption of Ni3 S2 and thus accelerate both the Volmer and Tafel steps in HER process. An excellent photoelectrochemical (PEC) performance with an onset potential of 0.54 V vs. reversible hydrogen electrode and an applied bias photon-to-current efficiency of 11.2% were obtained in MoS2 /Ni3 S2 /Ni/n + np + -Si photocathode under simulated AM1.5G illumination in 1 M KOH aqueous solution. Furthermore, comparing with the hybrid MoS2 @Ni3 S2 catalyst on Ni/Si with an inferior stability, the hierarchical MoS2 /Ni3 S2 structure releases the stress between the layers and leads to the stability of the photocathode with over 172-h PEC operation under 41.5 mA/cm 2 . This finding represents a potential low-cost and scalable approach toward making high performance, precious metal-free Si photocathodes for solar hydrogen production in alkaline media. Graphical abstract: Image 1 Highlights: Novel Si photocathodes for solar hydrogen production in alkaline electrolytes. The hierarchical MoS2 /Ni3 S2 structure provides abundant active sites for HER. Enhanced HER kinetics due to the atomic mixed interfaces in hierarchical MoS2 /Ni3 S2 . The highest ABPE of 11.2% reported among the Si based photocathodes.